PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN ONLINE MENGGUNAKAN GOOGLE CLASSROOM PADA MATERI ADMINISTRASI PAJAK KELAS XI AKL 1 SMK NEGERI 1 NEGARA - Ni Wayan Sri Tresna Egawati (Widyadari : Jurnal Pendidikan, 2022)
Discovery learning learning model is a student activity to understand the intent, meaning, concept and connect something by stimulating their intuitive so that they can draw a conclusion. However, it is still difficult to apply during the pandemic by studying online. The purpose of this study was to determine the response and application of the Discovery Learning learning model online using google classroom to improve student learning outcomes. This type of research is classroom action research. The subjects in the research were students of class XI AKL 1 State Vocational High School 1 State for the 2019/2020 academic year, while the object of this research was a study of understanding the subject of Tax Administration and student responses to the Discovery learning model. This study used several cycles including (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Based on the results of the study, it can be concluded (1) The application of the Discovery Learning learning model online using google classroom can improve student learning outcomes. (2) There is a positive response from students to the application of the Discovery Learning learning model online using Google Classroom to improve Tax Administration learning outcomes in class XI AKL 1 SMK Negeri 1 Negara for the academic year 2019/2020. This can be seen from the average value of the comparison pre-cycle, cycle I, and cycle II there is an increase